The role of regulator and NGOs in developing credit community and consumer sovereignty in Malaysia - Sandhu, Daljit Kaur; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Abd. Rahim @ Abd. Wahab, Husniyah (Universiti Putra Malaysia Press, 2022)
The purpose of regulating the Credit Community industry is to standardise moneylenders’ business compliance so that consumers may freely choose where to pursue their moneylending transactions. Media reported an increasing trend on breaching of consumers’ sovereignty by the moneylenders in Malaysia. Thus, the primary role of regulation effectiveness comes into the limelight. It raises the question of whether regulation enhancement supports or deter consumers’ sovereignty. The study was undertaken in Selangor and Kuala Lumpur, where most of the consumers’ issues were handled by non-governmental organisations (NGOs). The phenomenology approach was used to extract the three NGO leaders’ experiences and four regulator officers’ when dealing with the consumers and the licensed moneylenders’ issues. Data from semi-structured interviews and moneylending literature were uploaded into Nvivo 12 for thematic analysis. Findings revealed three themes: the non-governmental organisations’ role as the “watchdog”, the regulator’s educational role, and the regulator’s role in uplifting consumers’ sovereignty. The findings reveal a tendency for consumers with moneylending issues to seek NGOs, which affect the effort of seeking redress. The implication is for the regulator to take the lead in strengthening a three-way working relationship involving the moneylenders’ associations and the NGOs to resolve consumers sovereignty issues.